The effectiveness of internet marketing towards real estate in Malaysia / Muhammad Farid Omardin - Omardin, Muhammad Farid (2010)
Internet is a must have marketing tool used by most companies to market their business. Nowadays internet marketing is widely used in real estate sector. Some Real Estate Firms, Developers and Auctioneers take this idea seriously and belief internet marketing is one of the essential tool towards bring their products into the market. Some of real estate player took a step ahead by creating its own website in order to enhance the marketability of their product (project). In this research the author will measure the effectiveness of internet marketing to real estate scene in Malaysia. Besides the author will observe the effects that internet marketing brings towards real estate scene as a whole. In addition the author also will determine the essential elements in development of particular marketing in real estate sector. Conclusion of this study which will be based on the results and findings will be presented in the end of this paper.